Combinative application of pH‐zone‐refining and conventional high‐speed counter‐current chromatography for preparative separation of caged polyprenylated xanthones from gamboge. Issue 3 (21st December 2015) - Xu, Min; Fu, Wenwei; Zhang, Baojun; Tan, Hongsheng; Xiu, Yanfeng; Xu, Hongxi
Abstract : An efficient method for the preparative separation of four structurally similar caged xanthones from the crude extracts of gamboge was established, which involves the combination of pH‐zone‐refining counter‐current chromatography and conventional high‐speed counter‐current chromatography for the first time. pH‐zone‐refining counter‐current chromatography was performed with the solvent system composed of n ‐hexane/ethyl acetate/methanol/water (7:3:8:2, v/v/v/v), where 0.1% trifluoroacetic acid was added to the upper organic stationary phase as a retainer and 0.03% triethylamine was added to the aqueous mobile phase as an eluter. From 3.157 g of the crude extract, 1.134 g of gambogic acid, 180.5 mg of gambogenic acid and 572.9 mg of a mixture of two other caged polyprenylated xanthones were obtained. The mixture was further separated by conventional high‐speed counter‐current chromatography with a solvent system composed of n ‐hexane/ethyl acetate/methanol/water (5:5:10:5, v/v/v/v) and n ‐hexane/methyl tert ‐butyl ether/acetonitrile/water (8:2:6:4, v/v/v/v), yielding 11.6 mg of isogambogenic acid and 10.4 mg of β‐morellic acid from 218.0 mg of the mixture, respectively. The purities of all four of the compounds were over 95%, as determined by high‐performance liquid chromatography, and the chemical structures of the four compounds were confirmed by electrospray ionization mass spectrometry and NMR spectroscopy. The combinative application of pH‐zone‐refining counter‐current chromatography and conventional high‐speed counter‐current chromatography shows great advantages in isolating and enriching the caged polyprenylated xanthones.